A test of the efficient market hypothesis with regard to the exchange rates and the yield to maturity in Colombia (2016)
This article investigates the informational efficiency of the Colombian stock market with regard to the information contained in the exchange rates as well as the yield to maturity. Since the underlying data is non-normal with time-varying volatility we make use of tests that are based on bootstrap simulations with leverage adjustments in order to create reliable critical values. The results show that neither the exchange rates nor the yield to maturity is causing the stock price index. This is interpreted as empirical support for the efficient market hypothesis in that the Colombian stock market is with regard to these two main variables.